The Voice from the Shelf: 20 Years after the Smith Master's Thesis - Hummel, Banu F. (Routledge Journals, Taylor & Francis Ltd, 2018)
I have spent my professional life as a clinician and university instructor in divergent but connected roles, with one specific and recognizable aim: to facilitate the discovery of voice and insight in others that comes from opening dialogue and creating cohesion between our different selves-public and private, or professional and personal. It was only recently that I realized, quite unexpectedly, that my master's thesis was the prerequisite for this unspoken and repeated effort and that my relationship with my thesis advisor provided a model for how to bring forth such awareness. Now, 20 years later, I see myself engaged in a similar process in all aspects of my life. The Smith thesis was my initiation to this articulation, in print, of my personal and academic selves. As a tribute to the final tour of the Smith College School for Social Work master's thesis, and its farewell, I would like to tell this story.
Keywords: Master's Thesis; Finding And Facilitating Voice; Personal And Professional; Public And Private; Sexual Abuse; Writing; Therapeutic Process; Education; Mentorship